ETHNOCENTRISM ROLE ON THE RELATIONSHIP BETWEEN LOCAL/GLOBAL IDENTITY AND CUSTOMER ATTITUDE TOWARD LOCAL/GLOBAL POSITIONING AS PERCEIVED BY YOUNG INDONESIAN - Yulia A. Widyaningsih; Naila Zulfa; Teguh Budiarto (Journal of Applied Economics in Developing Countries, 2018)
There is a tendency for young people to identify themselves with global identity while also consuming local products. Our study aims to test whether ethnocentrism mediates the relationship between local identity and customer attitude toward local/global product positioning. The ethnocentrism measurement adapted CETSCALE with seven-point semantic differential scale. Data analysis adopted cluster and descriptive analysis. The respondents are two hundred young people, aged 17-34. This research found that global identity does not influence customer attitude toward products with global positioning. Ethnocentrism fully mediates the relationship between local identity and attitude toward products with local positioning. This research supports previous research that local identity positively influences ethnocentrism, while customer attitude toward products with global positioning does not correlate with ethnocentrism.Keywords: Ethnocentrism, Global/Local Positioning, Customer Attitude